The Impact of Quranic Readings on Alfiyya of Ibn Malik’s Grammar Systems - Fukara , Ebrahim Mohammed Hasan (Dirasat: Human and Social Sciences, 2024)
Objectives: This research aims to demonstrate the impact of frequent and unusual Quranic readings on Ibn Malik’s grammar systems in the book "Alfiyya of Ibn Malik." The study identifies instances where Ibn Malik refers to specific readings, such as the language in the five nouns, the distinction between homonyms, the prepositional vowels in nouns related to the dative pronoun, and so forth. The research seeks to highlight this influence and explore its significance, providing an analysis of the importance of Ibn Malik’s "Alfiyya" among experts and the relevance of Quranic readings. This research takes the first step, with a primary focus on everything related to readings associated with the verses of the book. Methods: The research employs a descriptive-analytical inductive approach to identify the owners of these readings, locate their occurrences, analyze them, and examine Ibn Malik’s interpretations. Results: Among the conclusions drawn by this research is Ibn Malik’s adeptness in adapting the language to suit his systems, serving as both a guide and a reference. He skillfully navigates complex linguistic concepts and incorporates them into his work. Notable examples include the nuanced handling of wishful thinking and the manipulation of intransitive pronouns. Conclusion: This research highlights Ibn Malik’s profound interest in Quranic readings and the significant impact they have on his selections and interpretations.